Ação coletiva e ato conectivo: dimensões e horizontes das relações entre as ruas e as redes - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
In this masters dissertation we seek to discuss the relationships between the recent manifestations of protest in Brazilian streets and the dynamic structure of social networks in telematic environments, specifically in the digital communication platforms like Twitter and Facebook websites. For this, we will start from the context of the June 2013 manifestations in Brazil, in order to investigate some of the intersections between connective acts and collective actions, as well as reflect on the possible implications of these intersections in the configuration and/or reconfiguration of a public opinion, of a public sphere and a communicational environment.
Collective action and connective act: dimensions and horizons of the relationship between streets and networks
Keywords: Manifestações públicas; Redes sociais on-line; Movimentos sociais; CIÊNCIAS HUMANAS: SOCIOLOGIA; Ação coletiva; Ato conectivo; Movimentos sociais; Redes sociais; Internet